2022
DOI: 10.21873/cgp.20357
|View full text |Cite
|
Sign up to set email alerts
|

Mesonephric-like Carcinosarcoma of the Uterine Corpus: Clinicopathological, Molecular and Prognostic Characteristics in Comparison With Uterine Mesonephric-like Adenocarcinoma and Conventional Endometrial Carcinosarcoma

Abstract: Background/Aim: This study aimed to investigate the clinicopathological, prognostic and molecular characteristics of uterine mesonephric-like carcinosarcoma (MLCS). Patients and Methods: We collected clinical,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 46 publications
(81 reference statements)
0
10
0
Order By: Relevance
“…Some studies did not examine the KRAS -mutational status of their reported cases and focused on morphologic findings and/ or clinical features (Pors et al 2021 ). Other studies performed molecular analyses but did not report the results in detail (Park et al 2022 ).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Some studies did not examine the KRAS -mutational status of their reported cases and focused on morphologic findings and/ or clinical features (Pors et al 2021 ). Other studies performed molecular analyses but did not report the results in detail (Park et al 2022 ).…”
Section: Resultsmentioning
confidence: 99%
“…On immunohistochemistry, MLA show negativity or limited positivity for estrogen receptor staining and positive staining for TTF-1, CD 10 (Fig. 1 e–g) and GATA-3 in most cases as well as for calretinin in some cases (Mirkovic et al 2018 ; Euscher et al 2020 ; Park et al 2022 ; McCluggage 2022 ).…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations